Prospects for seascape repair: Three case studies from eastern Australia. (2nd August 2019) - Creighton, Colin; Prahalad, Vishnu N.; McLeod, Ian; Sheaves, Marcus; Taylor, Matthew D.; Walshe, Terry
Summary: Three case studies spanning tropical, subtropical and temperate environments highlight the minimum potential benefits of investing in repair of coastal seascapes. Fisheries, a market benefit indicator readily understood by a range of stakeholders from policymakers to community advocates, were used as a surrogate for ecosystem services generated through seascape habitat restoration. For each case study, while recognising that biological information will always remain imperfect, the prospects for seascape repair are compelling.